Revolutionizing Health Care : Upfront Challenges in Implementation of Distributed Healthcare Management Systems - Saqib Rasheed; Muhammad Sajid Iqbal; Mahtab Khalid; Ahthasham Sajid; Mehak Saeed; Arshad Mehmood (Spectrum of Engineering Sciences, 2024)
This study employs a systematic literature review (SLR) to investigate the initial obstacles encountered when implementing distributed healthcare management systems as means to transform healthcare delivery. This article delves into healthcare IT adoption challenges through a multi-faceted lens, evaluating key studies that explore organizational, technological, regulatory, stakeholder, financial, governance, and cultural considerations. We examine leadership pushback, incompatibility, compliance, and cultural adaptation. Longitudinal studies and practical frameworks are proposed for future research; however, the authors acknowledge the technical limitations of the present literature and study selection biases. By addressing these issues, stakeholders may increase healthcare delivery system adoption and technology integration. Keywords: Distributed healthcare management systems, challenges, systematic literature review